2003
DOI: 10.2320/matertrans.44.1438
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy of Interfaces in Joints between Pb-Free Solders and Electroless Ni-P

Abstract: Microstructures of joints between a Ni-8 mass%P UBM (under bump metallization) and three different Pb-free solders, i.e., Sn-Ag, SnAg-Cu and Sn-Ag-Cu-Bi were studied by transmission electron microscopy. The phases formed near the joint interfaces as well as inside the solders during soldering were identified on the basis of electron diffraction and EDX analysis without ambiguity. In the Ni-P under bump metallization near the interface with the solders, P-denuded Ni-20 mass%P layer was observed, where a high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…[15][16][17][18][19][20] Hwang et al examined the interfacial reaction between the Sn-3.5Ag solder and Au (0.06 lm)/ Ni-6wt.%P (5 lm) plated layer at a reflow temperature of 230°C for 40 s and reported that Ni 3 SnP formed on top of the Ni 3 P layer in Sn-3.5Ag/Ni-P joints. 20 Lin and Duh reported the transformation of Ni 2 P-Ni 2 SnP as a result of the in-diffusion of Sn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20] Hwang et al examined the interfacial reaction between the Sn-3.5Ag solder and Au (0.06 lm)/ Ni-6wt.%P (5 lm) plated layer at a reflow temperature of 230°C for 40 s and reported that Ni 3 SnP formed on top of the Ni 3 P layer in Sn-3.5Ag/Ni-P joints. 20 Lin and Duh reported the transformation of Ni 2 P-Ni 2 SnP as a result of the in-diffusion of Sn.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the many different solder alloys that have been proposed as potential Pb-free solders, the alloy families of Sn-Ag and Sn-Ag-Cu have shown the greatest promise. 4,11 In addition to solder, printed circuit boards (PCBs) and component surface finishes also need to be Pb-free.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCl for 24-48 h with intermittent cleansing in detergent solution in ultrasonic cleaning environment and a large number of small crystals are freed from ingot in this manner. Torazawa et al [51] using transmission electron microscopy (TEM) study confirmed the crystal structure of Ag 3 Sn as Pmmn (59) without ambiguity. The crystal structure of Ag 3 Sn is shown in Fig.…”
Section: Methodsmentioning
confidence: 93%
“…However, a Ni-Sn-P phase formed between IMCs and Ni-P UBM causes IMCs to be spalled into the solder matrix, resulting in a reliability concern. [14][15][16][17][18][19][20][21][22] More recently, the detailed formation configuration for Ni x P y layers and Ni-Sn-P in the Sn-Ag-Cu/Ni-P UBM solder joint was intensively investigated with a newly developed field emission electron probe microanalyzer. 22 It is argued that the formation of Ni-Sn-P is significantly dependent on the phosphorous content of Ni-P UBM.…”
Section: Introductionmentioning
confidence: 99%